(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The article analyses two songs created by Eduardo Dussek and Luiz Carlos Góes for the Brazilian Musical Theater. Here the songs analyzed are Alô, Alô, Brasil, composed by Dussek for the show Feiticeira, casting Marília Pêra, in 1975, and A Loura do Carteado, written by him alongside Góes. This was written for the travesti Rogéria to sing in Rio Gay, acting that starred in Teatro Alaska, Rio de Janeiro. The cast composed by travestis whose aesthetics brought back to life the golden times of Teatro de Revista in Brazil. In the article there is as well the description of the beginning of Dussek’s theatrical career, revisiting his acting, when he was still a teenager, in the show As Desgraças de uma Criança, by Martins Pena, directed by Antônio Pedro.